Drug resistance and phylogenetic grouping of bacteria isolated from visitors' hands in a secondary-care hospital - Samuel Campista-León; María José Cabanillas-Pacheco; Laura de Jesús Delgado-Díaz; Joel Tohevaris Garcia-Guerrero; Luz Isela Peinado-Guevara (Journal of Infection in Developing Countries)
Introduction: Dynamic movement in the hospital environment promotes the transmission of nosocomial pathogens and multidrug resistance mechanisms through the dissemination of organisms that carry genetic determinants. Healthcare workers play an important role in the spread of pathogens; however, the role of visitors in this environment is poorly understood.